Agendas, Horizons, and the Canadian Introductory Reader / Biggs, C. Lesley, Susan Gingell, and Pamela J. Downe, eds. 2011. Gendered Intersections: An Introduction to Women’s and Gender Studies. Second Edition. Halifax, NS: Fernwood / Crow, Barbara, and Lise Gotell, eds. 2009. Open Boundaries: A Canadian Women’s Studies Reader. Third Edition. Toronto, ON: Pearson Prentice Hall / Hobbs, Margaret, and Carla Rice, eds. 2013. Gender and Women’s Studies in Canada: Critical Terrain. Toronto, ON: Women’s Press - Parkins, Ilya (Atlantis, 2016)
This essay reviews three Canadian Introduction to Gender and Women’s Studies readers, asking what they might reveal about the investments and values that animate teaching in Gender and Women’s Studies. It argues that the texts are incommensurable with current theoretical and methodological trends in Gender and Women’s Studies and considers what each offers to the field.